2016
DOI: 10.1007/s10995-016-2124-8
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Childbearing and Child Growth in Northern Malawi

Abstract: Objective The study aims to assess whether unintended children experience slower growth than intended children. Methods We analysed longitudinal data linked to the Karonga Health and Demographic Surveillance Site collected over three rounds between 2008 and 2011 on women’s fertility intentions and anthropometric data of children. Using the prospective information on fertility intention we assessed whether unintended children are more likely to be stunted than intended children. We applied Propensity Score Matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 24 publications
1
29
1
2
Order By: Relevance
“…Studies in Nepal, Kenya and Peru have found unwanted pregnancies to be associated with incomplete vaccination statuses by the child's first birthday (Marston and Cleland 2003;Echaiz et al 2018), but no relationship was found in Bolivia and the Philippines (Marston and Cleland 2003). Likewise, for nutritional status, children of unwanted pregnancies in Bangladesh were more likely to be stunted, wasted and underweight (Rahman 2015); however, no effect was found between pregnancy intention and stunting in Malawi (Baschieri et al 2017). The inconsistency between our results and the previous findings could Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in Nepal, Kenya and Peru have found unwanted pregnancies to be associated with incomplete vaccination statuses by the child's first birthday (Marston and Cleland 2003;Echaiz et al 2018), but no relationship was found in Bolivia and the Philippines (Marston and Cleland 2003). Likewise, for nutritional status, children of unwanted pregnancies in Bangladesh were more likely to be stunted, wasted and underweight (Rahman 2015); however, no effect was found between pregnancy intention and stunting in Malawi (Baschieri et al 2017). The inconsistency between our results and the previous findings could Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the extant literature (Marston and Cleland 2003;Hajizadeh et al 2015;Rahman 2015;Rahman et al 2016;Baschieri et al 2017; Hajizadeh 2019), we controlled for birth characteristics (gender, age of child, birth order) and household-level covariates (mother's age at birth, mother's marital status, mother's education, household living standard/wealth and region) that have been consistently collected in all DHS surveys and country-level covariates [GDP per capita and public health expenditures per capita in purchasing power parity (PPP), 2011 prices, international $] in our analysis. A constructed wealth index (WI) for each household in the DHS surveys was used as a measure of the household living standard.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, WHO released new recommendations regarding antenatal care for a positive pregnancy experience. The WHO states that at least eight antenatal visits are recommended to reduce perinatal mortality, increasing overall quality of antenatal care and improving maternal satisfaction [17]. In the present study, data collection only occurred at healthcare facilities, so all the study participants had at least one antenatal visit; however, the participants may have been in various trimesters of pregnancy and may have had additional visits after the study.…”
Section: Antenatal Care and Supplementationmentioning
confidence: 98%
“…Se ha identificado que la gran mayoría de los estudios, analizados para la elaboración del presente trabajo, se enfoca en la asociación entre la intención de la madre con los indicadores de crecimiento del niño mas no en las prácticas beneficiosas, como la suplementación con hierro, la lactancia materna exclusiva, la lactancia la primera hora de vida, etc. (8)(9)(10). No obstante, como se evidencia, la importancia de prácticas nutricionales correctas durante y después del embarazo, son necesarias para asegurar el adecuado crecimiento y desarrollo de los niños (10).…”
Section: Conclusiónunclassified